The Role of Educator Stimulation in Dealing with Speech Delay of 4–5 Years-Old Children at RA Hidayatullah Pamekasan - Arifin, Hennyatul Dwi (Universitas Pendidikan Indonesia Kampus Serang, 2024)
Speech delays are one of the causes of developmental disorders that are often found in children. Delayed speech is a serious problem and needs immediate treatment. This research aims to find the stimulation of educators, the learning media, and the obstacles and supporting factors in dealing with 4-5-year-old children with speech delay located at RA Hidayatullah Pamekasan. This research uses a descriptive method and a qualitative approach. Data collection instruments used were interviews, observation, and documentation. The stimulations provided for children at RA Hidayatullah Pamekasan by the teachers are reading story books together, singing, and playing with puzzles and legos to trigger new vocabulary. Some media applied are storybooks and puzzles to stimulate children to talk flawlessly into correct patterns and to add new vocabulary. The media are chosen as they become effective tools to overcome speech delay difficulties and support the activities. Several factors support and challenge teachers in stimulating students with speech delays. Less stimulation provided by parents in daily life is the most inhibiting factor. In conclusion, educators have a very important role in stimulating children, especially in selecting learning activities and media for teaching students with speech delay but parents have a specific role in the whole language development stimulation. The teacher's role will be optimal by the support of the parent’s role.